Halal issues in the mammalian cell culture for recombinant protein production - Arief Ichwan, Solachuddin Jauhari (2013)
Awareness and interest in halal products has significantly increased among muslim and non-muslim countries. Biopharmaceutical products including recombinant therapeutic proteins contribute to a considerable percentage in the worth of the overall global halal industry, which is said to be US$ 2.3 trillion. The number and demand for approved biopharmaceutical products produced from mammalian cell culture methods such as vaccines, monoclonal antibodies, antibodies, hormones, and other therapeutic proteins are increasing worldwide. The mammalian cell culture technology has been known to be perfectly suited to the production of recombinant therapeutic proteins. Mammalian cell culture is a general term used for the isolation of the cells of a mammalian from specific tissues further cultured and reproduced in an artificial growth media. The overall process in the recombinant protein synthesis using mammalian cell culture involves the use ingredients or materials that may be questioned from the perspective of halal procedures that make the product cannot fulfill the requirements of halal pharmaceuticals. This review will discuss the application of mammalian cell culture bioprocesses in recombinant biopharmaceutical protein production with focus on the halal-compliance status of the materials and methods.